Iterative piezo response function-based optimization for static shape control of cantilever beam using nonlinear piezoactuators. (1st January 2023) - Sumit; Kane, S R; Sinha, A K; Ganguli, Tapas; Shukla, Rahul
Abstract: Shape control of complex structures by optimizing the electrode potential is not achievable directly by analytical solutions and piezo response function base-optimization techniques due to the nonlinear response of piezoactuators. In the present work, a metaheuristic iterative piezo response function (iPRF)-based optimization technique is developed to achieve the arbitrary shape of piezoelectric unimorph (PU) using nonlinear piezoactuators. In this regard, a PU is fabricated using APC 850 piezoactuator to verify the nonlinear response in bending mode and nonlinear analytical model of PU. After verification, length of the inactive layer and number of piezoactuators in PU are modified to study the shape control. iPRF-based technique is used for the optimization of electric potential to achieve the target shape of modified piezoelectric unimorph (MPU) with various piezoactuators. The results of iPRF-based technique are compared with the results of simulated annealing (SA)-based direct optimization technique. Unlike SA-based direct optimization technique, prior knowledge of nonlinear coefficients of piezoactuator is not required in iPRF-based technique. Optimum values obtained from both the direct nonlinear solution- and iPRF-based optimization methods are same for all MPUs. Furthermore, the number of iterations of iPRF-based optimization approach is not affected by the number of piezoactuators used to achieve the desired shape.